Ye feng fei wu - Huang, Beijia 1955- (Huang Bei jia qing qing xiao shuo xi lie, 2024)
"Nanjing, China, 1937. Eight-year-old Orange is uprooted from her comfortable home when the family is forced to flee from Japanese bombing raids. They take refuge in Chengdu, West China, where she grows up with her professor father, hard-working mother, two sisters, two brothers and Tianlu, a war orphan. At first, the irrepressible Orange hardly notices how hard life is for the adults around her. She is much too busy having adventures and getting into the inevitable scrapes. Her life is full of laughter, and the music that her family and their friends make. But as she comes of age and the war creeps closer, she begins to learn the joys and heartbreak of love and loss." -- back cover of English edition (Balestier Press, 2022. ISBN 978-1-913891-34-3)